Facial pain of cardiac origin: a case report - Franco, Ana Carolina de Oliveira; Siqueira, José Tadeu Tesseroli de; Mansur, Alfredo José (São Paulo Medical Journal, 2006)
CONTEXT: Cardiac pain may radiate to the face and lead patients to seek dental care. Dentists may contribute towards the diagnosing of isch- emic heart disease and thus refer patients for cardiological evaluation. CASE REPORT: A 50-year-old female patient was referred to a dentist for evaluation of a suspected temporomandibular disorder after repeated visits to medical emergency departments due to excru- ciating facial and left temporal pain associated with exertion. The pain would start in the chest and radiate to the neck, face and left temporal region. The patient’s chief complaint was the facial pain; hence, she sought dental care. The dental examination revealed an edentulous up- per jaw and partially edentulous lower jaw with full upper prosthetic set of teeth and decreased vertical dimension. X-ray of facial bones did not reveal any bone abnormalities. A diagnosis of temporomandibular disorder was made. How- ever, she was referred for cardiological evalu- ation, since her pain was starting in the chest and because she had a past medical history of surgical treatment for coronary artery disease. A diagnosis of angina pectoris was made, the therapeutic regimen was optimized and her angina was brought under control.